PENDIDIKAN IPS SEBAGAI WADAH PENGUATAN NILAI BUDAYA LOKAL DI ERA GLOBALISASI - kariadi, dodik (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Local cultural value if it is not preserved and maintained, it is feared gradually will experience the process of extinction due to the influence of globalization. One of the efforts to preserve it is through the utilization of local culture in the learning process in schools. IPS as a lesson that holds a significant role to develop the culture is expected to be a forum for local culture available. IPS Learning in school is expected to develop a range of capabilities on students, especially the ability to live in the middle of a neighborhood or community where students live. Therefore, teachers are required to have an adequate understanding of the value of local culture, in addition to its ability to understand the subject matter of responsibility.